Take flying to the masses: a regulatory governance perspective. (24th November 2021) - Mishra, Brajesh; Tapasvi, S.K.; Panda, Abinash
This paper investigates why the Indian civil aviation sector, liberalised back in the 1990s, could not adequately promote regional air connectivity. It has identified various regulatory gaps and measures needed to attain the civil aviation policy goal 'take flying to masses'. An exploratory case study approach has been adopted since the study deals with a specific issue, namely, regional and remote air-connectivity in India. The case context is built up by collating information about: 1) the structure and performance of the aviation industry; 2) related policy/regulatory governance framework. Data collection from multiple sources (research articles, industry reports, regulatory/policy documents, and semi-structured interviews with experts) has resulted in the triangulation of data and enriched analysis, thereby ensuring greater reliability and validity of research outcomes. This study's findings add to the academic knowledge space of regulation in the global south, particularly regulatory implementation in the Indian civil aviation sector.